Testing a modified electronic version of the Edmonton symptom assessment system-revised for remote online completion with ambulatory cancer patients in Alberta, Canada - Linda Watson; Claire Link; Siwei Qi; Andrea DeIure; Lindsi Chmielewski; April Hildebrand; Louise Smith; Lisa Barbera (Digital Health, 2023)
Objective The cancer program in Alberta, Canada routinely collects patient-reported outcomes using the Edmonton symptom assessment system-revised (ESAS-r). The program recently launched the province's new clinical information system which has expanded functionality, allowing patients to complete symptom questionnaires remotely online, instead of completing a paper form at the clinic. This study aimed to test a modified electronic version of the ESAS-r [(e)ESAS-r] with patients, to assess the feasibility of completion and questionnaire clarity. Methods Staff, patients, and other stakeholders worked to create modified definitions for ESAS-r symptoms, to aid in patient understanding. Patient and family advisors were recruited to test the questionnaire. Participants completed an online mock-up of the (e)ESAS-r and answered questions about technical issues. One-to-one cognitive interviews were held to discuss each symptom definition in detail. Modifications were made based on the feedback and a second round of interviews was held to finalize the wording. Results In total, 19 patients and 7 family advisors participated. All but one (96.2%) completed the questionnaire without assistance and had no technical issues. Participants requested certain wording modifications and that definitions be added for all symptoms for consistency. Very few participants reported any confusion with the final definitions. Conclusions The (e)ESAS-r was tested for clarity and ease of completion and was determined to be suitable for remote online use with ambulatory cancer patients. The enhanced definitions on the new questionnaire were clear to patients and helped ensure they understood the meaning of each symptom they were asked to rate.